Enhanced biosorption of cadmium ions on immobilized surface-engineered yeast using cadmium-binding peptides - Wang, Songting; Sun, Yongmei; Wang, Shihong; Fan, Chunkun; Wang, Daojie; Liu, Fei; Zhang, Haiyan (Frontiers in Microbiology, 2024)
A new type of cadmium (Cd) ion cell surface adsorbent was developed by integrating bacteriophage display peptide library technology with cell surface display technology. Cd2+ chelating resin served as the target molecule in screening experiments, leading to the identification of four Cd2+ −binding peptides. These peptides were introduced into Saccharomyces cerevisiae via the pYD1 plasmid using lithium acetate heat shock transformation. Adsorption efficiency tests indicated that the engineered yeasts adsorbed more Cd2+ than the control strain EBY100 when exposed to the same amount of Cd2+. Among these peptides, sequence 3-containing strain was demonstrated to have the highest Cd2+ adsorption efficiency, being 35% higher than the control strain. Additionally, when this recombinant yeast strain was immobilized using sodium alginate, the adsorption efficiency was increased by 55.7% compared to the control strain.